The Identification of the Existence of a Fault Structure on Gravity and Audio Magnetotulleric Data in the Area of Mount Kubing, Belitung - Sanjaya, Edi; Nafian, Muhammad; Suwondo, Suwondo; Fadillah , Muhammad Hasnan; Shafa, Dias (Universitas Negeri Surabaya, 2023)
Mount Kubing holds significant potential as a tourist attraction, despite being situated in a tectonic zone prone to faults. Its size and attractions make it suitable for both travel and exploration. Hence, the study has been conducted to identify subsurface structures that can identify the structural fault lines when the mitigation occurred during an earthquake or landslide. The derivative analysis method is used to determine the type of structures. The results of the derivative analysis indicate the direction of the fault structure on a Northwest-Southeast, and Southwest -Northeast that is controlled by two different faults. The fault caused by depression from granitic body and silt with FHD and SVD gravity value around -3 mGal until 1 mGal that showing the indication of normal fault and reverse fault in the research location with depth estimation curve (RAPS) approximately 500 meters in the subsurface of the earth. Whereas in 2D Audio Magnetotelluric modelling, it is identified that the groundwater reservoir layer is at a depth of 70-85 meters below the surface which is recognized as a semi-stressed reservoir with a value of 20-27 mv/nT in complex silt and sandstone.